A year-long monitoring of preloaded free-maintenance bolts – Estimation of preload loss on BobTail bolts. (February 2018) - Matos, R.; Shah Mohammadi, M.R.; Rebelo, C.
Abstract: In order to allow an increase in the height of the towers to exploit stronger and more stable wind profiles, a welded-free friction connection was proposed for the new generation of wind towers. This geometry requires a reliable estimation of the bolts' performance over time and a free maintenance bolt is demanded since no access to the outside of the tower is possible. This paper illustrates the monitoring of such a bolted connection prototype with focus on the behaviour of free maintenance BobTail ® bolts, which allows the tightening from the inner side of the tower. The monitoring and identification procedure for the 1-year monitoring of the force and the temperature in a prototype is presented. A calibrated nonlinear Hammerstein-Wiener model is used to withdraw the temperature effect from the analysis allowing for a long-term estimation of the preload losses. This model is able to simulate the force with less than 2.5% of error. The significant part of the preload loss was foreseen within the first two years. Furthermore, the influence of the tightening temperature on the bolts loss was discussed and, as expected the lower the temperature during tightening, the lower the long term preload losses. Highlights: Estimation of the long-term losses of free maintenance bolts installed in a friction connection of wind tower prototype. Feasibility and accuracy of the tightening procedure of BobTail bolts. Influence of the tightening sequence of bolts in friction connections. System identification using a nonlinear Hammerstein-Wiener model and extrapolation for the 20-year lifespan of the tower.